Haematology of Clarias gariepinus exposed to Microcystin-LR - Patrick Omoregie Isibor (Beni-Suef University Journal of Basic and Applied Sciences, 2017)
A static bioassay experiment was conducted by exposing Clarias gariepinus to 200 µg/L and 400µ/L of MC-LR solutions for 14 days and 28 days to assess the haematological impacts such as estimation of red blood cells, white blood cell and Thrombocytes, haemoglobin percentage, haematocrit, and percentage changes. A dramatic reduction was observed in the RBCs in both experimental cases after 28 days; which can be attributed to haemolysis. Result showed significant impact of MC-LR on RBCs counts on duration (28 days) basis; regardless of the concentrations. The PCV after 28 days was significantly lower than that observed after 14 days, which was also significantly lower than that observed in the control set-up. The concentrations; particularly 400 µg/L MC-LR exerted significant stress on the fish. A general temporal increase was recorded in the total count of WBCs in both experimental cases. Results showed that MC-LR; particularly 400 µg/L caused significant haematological disruptions in the C. gariepinus, especially after 28 days of exposure i.e. 400 µg/L (28 days) > 400 µg/L (14 days) > 200 µg/L (28 days) > 200 µg/L (14 days). Due to the fact that natural aquatic ecosystems affected with algal bloom contain concentrations of MC-LR higher than the experimented levels, aquatic biota in affected water bodies are liable to suffer worse consequences than those observed in this experiment. This necessitates proactive measures on susceptible water bodies in order to forestall liable debilitating effects on the aquatic biota.